2020
DOI: 10.1590/s1677-5538.ibju.2019.0225
|View full text |Cite
|
Sign up to set email alerts
|

Bone scan positivity in non-metastatic, castrate-resistant prostate cancer: external validation study

Abstract: Introduction: Tables predicting the probability of a positive bone scan in men with non-metastatic, castrate-resistant prostate cancer have recently been reported. We performed an external validation study of these bone scan positivity tables. Materials and Methods: We performed a retrospective cohort study of patients seen at a tertiary care medical center (1996-2012) to select patients with non-metastatic, castrate-resistant prostate cancer. Abstracted data included demographic, anthropometric, and disease-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…There are no specific clinical manifestations in the early stage of prostate cancer, and many patients have metastasized at the time of first diagnosis and lost the best time for treatment, leading to treatment failu-re. Therefore, finding effective diagnostic methods and indicators for early diagnosis of prostate cancer is the key to improve the cure rate as well as the survival rate (20,21). Imaging examination plays an important role in the clinical diagnosis and staging of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There are no specific clinical manifestations in the early stage of prostate cancer, and many patients have metastasized at the time of first diagnosis and lost the best time for treatment, leading to treatment failu-re. Therefore, finding effective diagnostic methods and indicators for early diagnosis of prostate cancer is the key to improve the cure rate as well as the survival rate (20,21). Imaging examination plays an important role in the clinical diagnosis and staging of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate specific antigen (PSA) levels are often used as an indication for the presence of bone metastases and have been used as a gate-keeper to determine the need for bone imaging. A study carried out by Johnston et al [ 4 ] showed that a higher PSA at scan was significantly predictive of bone scan positivity ( P < .0001). Various studies have also assessed the value of alkaline phosphatase (ALP) in the prediction of bone metastases and suggested that ALP may be the more reliable indicator when stratifying the extent of bone metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Johnston and colleagues from USA ( 5 ) performed on page 42 an external validation study about bone scan positivity in non-metastatic, castrate-resistant prostate cancer. The authors performed a retrospective cohort study of 6,509 patients with non-metastatic, castrate-resistant prostate cancer and concluded that previously published risk tables predicted bone scan positivity in men with non-metastatic, castrate-resistant prostate cancer with reasonable accuracy.…”
mentioning
confidence: 99%